Two‐Dimensional Materials for Beyond‐Lithium‐Ion Batteries. Issue 11 (15th March 2016) - Peng, Lele; Zhu, Yue; Chen, Dahong; Ruoff, Rodney S.; Yu, Guihua
Abstract : Lithium‐ion batteries (LIBs) have dominated the portable electronics industry and solid‐state electrochemical research and development for the past two decades. In light of possible concerns over the cost and future availability of lithium, sodium‐ion batteries (SIBs) and other new technologies have emerged as candidates for large‐scale stationary energy storage. Research in these technologies has increased dramatically with a focus on the development of new materials for both the positive and negative electrodes that can enhance the cycling stability, rate capability, and energy density. Two‐dimensional (2D) materials are showing promise for many energy‐related applications and particularly for energy storage, because of the efficient ion transport between the layers and the large surface areas available for improved ion adsorption and faster surface redox reactions. Recent research highlights on the use of 2D materials in these future 'beyond‐lithium‐ion' battery systems are reviewed, and strategies to address challenges are discussed as well as their prospects. Abstract : Two‐dimensional nanomaterials have gained growing interest as promising candidates for electrode materials for lithium ion batteries and beyond. Various kinds of two‐dimensional nanomaterials for sodium ion batteries and other emerging battery technologies are summarized, along with the current difficulties and potential strategies. Perspectives on the future development of two‐dimensional nanomaterials as beyond‐Li‐ion energy storage electrodes are presented.